2021
DOI: 10.31557/apjcp.2021.22.9.2969
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) Prevalence and Type Distribution in Urban Areas of Malaysia

Abstract: Background: Cervical cancer is the third leading cause of death in Malaysia, and Human Papilloma Virus (HPV) is the principal aetiology that is responsible for its development. This study was aimed to determine the prevalence and distribution of HPV types among different age groups, ethnicity, and areas in Malaysia. Materials and Methods: A total of 764 women aged 20-74 years old within the cities of Johor Bahru, Kuala Lumpur, Ipoh, Penang, and Kota Kinabalu underwent both cervical cytological assessment and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Non-vaccine types of significant prevalence in geographical regions include HPV 39, 52, 68 and 81. HPV 52 and 58 were found to be the most prevalent types in a study in Ghana [ 33 ] and HPV 52 was the most prevalent type in a recent study in Malaysian women [ 34 ]. In addition to HPV 52, HPV 68 and HPV 81 have found to be prevalent in China [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-vaccine types of significant prevalence in geographical regions include HPV 39, 52, 68 and 81. HPV 52 and 58 were found to be the most prevalent types in a study in Ghana [ 33 ] and HPV 52 was the most prevalent type in a recent study in Malaysian women [ 34 ]. In addition to HPV 52, HPV 68 and HPV 81 have found to be prevalent in China [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two most important proteins in the carcinogenesis of cervical cancer are E6 and E7, which are responsible for the dysregulation of the cell cycle [ 67 ]. A study by Rahmat et al 2021 showed that the most common high-risk HPV type among women living in urban areas in Malaysia is HPV 52, which is not the type of infection the current HPV vaccine is covered for protection among females [ 68 ]. This data is very important because it might evidence to the stakeholders on why cervical cancers is still increasing in Malaysia despite the vaccines given.…”
Section: Top Of Formmentioning
confidence: 99%
“…AiM Reader (DR. Chip Biotech, Inc., Miaoli, Taiwan). 18 F I G U R E 1 Schematic diagrams of various components and procedures related to the self-sampling device and sample processing procedures in this study. (a) The self-sampling device provided to participants for the study is approximately 10 cm long, with a comfortable grip handle measuring 2.3 cm and a polyurethane foam sample collection pad embedded in the distal end.…”
Section: Sample Processing and Hpv Screeningmentioning
confidence: 99%